Integrating indigenous knowledge for participatory land use planning (PLUP) in Tra Hat hamlet, a climate-smart village in the Mekong River Delta, Vietnam - Thanh Vu Pham; Hieu Trung Nguyen; Tuan Huy Vuong; Pham Dang Tri Van; Quang Tri Le (Vietnam Journal of Science, Technology and Engineering, 2017)
Agriculture is a primary source of livelihood in the Vietnamese Mekong River Delta with different land use activities. There are different potential conflicts in agricultural land use, including: water resources use and interests. Therefore, establishing feasible land use planning (LUP) in an area needs an in-depth participation and discussion among stakeholders (including: governments at different levels, local farmers, and national and international scientists). Indigenous knowledge of local farmers plays an important role in making land use decision, which can support solving land-use conflicts to achieve the most sustainable management of land resources. In this study, we integrated local knowledge into a land use planning process to assess the suitability of land use types and to project potential impacts of climate change conditions on land use decisions in the Tra Hat hamlet, one of the climate-smart village (CSV) sites in the Vietnamese Mekong River Delta. A total of two consultation meetings, using simple tools (resources mapping, timeline, seasonal calendar, wealth ranking, Venn diagram, pair wise ranking, and key informants’ interviews), were conducted, and 130 households were interviewed during a field visit in 2015. As a result, a participatory land use planning (PLUP) was implemented with active participation of the concerned communities to establish a suitable land use planning and identify the potential adaptation techniques in the near future (2020). Land use planning at the hamlet was discussed to get the agreement and the coordination among local governments, farmers and scientists on adaptation practices.